Punishment is not a group adaptation: humans punish to restore fairness rather than to support group cooperation - Baumard, N (Springer, 2011)
Punitive behaviours are often assumed to be the result of an instinct for punishment. This instinct would have evolved to punish wrongdoers and it would be the evidence that cooperation has evolved by group selection. Here, I propose an alternative theory according to which punishment is not an adaptation and that there was no specific selective pressure to inflict costs on wrongdoers in the ancestral environment. In this theory, cooperation evolved through partner choice for mutual advantage. In the ancestral environment, individuals were in competition to be recruited in cooperative ventures and it was vital to share the benefits of cooperation in a mutually advantageous manner. If individuals took a bigger share of the benefits, their partners would leave them for more interesting partners. If they took a smaller share, they would be exploited by their partners who would receive more than what they had contributed to produce. This competition led to the seleciton of a sense of fairness, a cognitive adaptation aiming to share equally the benefits of cooperation in order to attract partners. In this theory, punishment is not necessary for the evolution of cooperation. Punitive behaviours are only a way to restore fairness by compensating the victim or penalizing the culprit. Drawing on behavioural economics, legal anthropology, and cognitive psychology, I show that empirical data fit better with this framework than with the theory of group selection. When people punish, they do so to restore fairness rather than to help the group.